Plasma levels of LH and testosterone in male rats subjected peripheral de-afferentation of the vomeronasal system (Revista Española de Fisiología, 1984)
21 day old male rats undergoing peripheral deafferentation of the vomeronasal system (Accessory Olfactory System) show a decrease of the accessory sex organ weight as well as lower LH and testosterone plasmatic levels 30 days later when compared with intact or sham operated rats.